Pemetaan Pola Progresi Chord Berdasarkan Kombinasi Interval - Ilham Pamuji (Pascasarjana ISBI Bandung, 2020)
Various phenomena, concepts and theories in music can be explained by mathematics. Moreover, it can be an approach in the process of song creation, composition, or music arrangement. Related to this, this study discusses the mapping of chord progressions based on interval combinations in chromatic circles. To be more specific, by connecting the musical notes with lines that represent various combinations of two specific types of intervals into a series of notes (chord progression patterns) in one loop ( starts and ends at note C). The interval combination pattern refers to the smallest size, namely m2 (minor second /minor second, 1 semitone step). This research was conducted to produce various patterns of unconventional chord progression patterns viewed through a tonal harmony system. This research is motivated by the strong influence of the tonal harmony system limiting creativity in the music creation process. Therefore, it takes an approach, method, or other system that needs to be tested to get out of the system. The result of this research is that there are 32 variations of chord progression patterns (series of notes) which are summarized in geometric shapes. By comparing the geometric shapes, the patterns appear mathematically, systematic, and symmetrical. In its application, these patterns seem unconventional, come out of a tonal harmony system (it can still be studied through the system, depending on the chord shape used) and produce a unique sound.Keywords: chord progression, interval, chromatic circle, music creation